Farewell to Europe’s Horizon 2020 - Abbott, Alison (Nature (London), 2020)
Although imperfect, the world’s biggest funding scheme got a lot right. Although imperfect, the world’s biggest funding scheme got a lot right. "Outrage became the exception, and my stories became less colourful."